Engineering mathematics - Pal, Srimanta (Oxford Univ Press, 2015)
Engineering Mathematics is a textbook written for undergraduate students of all streams of engineering. This book exhaustively covers all the topics taught in mathematics in different semesters in the B. Tech curriculum. Beginning with the basics, the book first introduces mathematics and its nuances to the students and explains the difference between applied mathematics and engineering mathematics. Fundamental topics such as sequence and series and matrices are discussed with the applications to engineeringapplications to engineering problems. Other important topics such as three dimensional geometry, functions of single variable and several variables, differential calculus, integral calculus, Fourier series, Fourier transform, Fourier integrals, ordinary differential equations, partial differentialequations, special functions, vector calculus, complex analysis, and Laplace transform have been discussed in detail. Separate chapters are dedicated to probability, statistics, numerical methods, and discrete mathematics. Most of the chapters comprise sections on applications to engineeringproblems. There are separate chapters discussing the applications of the mathematical theorems and numerical methods to engineering problems. Plenty of solved examples, review questions, numerical exercises, and multiple choice questions have been provided to ensure that students get enough practice.
Includes index.
Keywords: Engineering mathematics.; elektronické knihy; electronic books